It takes a village; a cancer rehabilitation center focusing on community and support for cancer- affected - Elfvelin, Nelly (My University, 2025)
This thesis investigates how architecture can bridge the gap in Sweden between clinical cancer care in hospital environments and the psychosocial support offered by community support initiatives for cancer-affected individuals. Although hospitals do offer essential medical care and nonprofit centers such as Kraftens Hus do provide emotional and psychological support services, many cancer-affected, including patients and their loved ones, struggle with the transition between these two phases of care. Through this study, a set of architectural design strategies that foster homeliness, biophilic design, social interaction and therapeutic environments are identified via literature reviews, interviews with health-care professionals and case studies such as Maggie’s Centers and Center for Kraeft og Sundhed. These design strategies form a design proposal for a rehabilitation center in Örebro, located in close proximity to the main university hospital in the city. The proposal emphasizes integration of greenspaces and daylight, as well as therapeutic environments constructed for flexible spaces supporting rest, physical activity and social interaction. Moreover, it highlights the importance of connection to nature, health promoting environments and the smooth transitions between different spatial zones, from active to calmer areas. The project aims to create a well balanced care environment, inclusive of diverse cancer-affected individuals, while promoting healing, belonging and a more holistic approach to cancer rehabilitation, ultimately bridging the gap between medical cancer treatment and long-term psychosocial support
Keywords: Biophilic design, Homeliness, Therapeutic environments, Cancer reha bilitation, Community in cancer rehabili tation, Social support